Caprellidae (Crustacea: Amphipoda) of Aotearoa New Zealand waters: a constantly changing landscape - Peart, Rachael A.; Woods, Chris (Zootaxa, 2025)
A snapshot of the changing landscape of the Aotearoa New Zealand caprellid fauna is presented. This study is primarily an examination of historic material, mainly from the NIWA Invertebrate Collection. The caprellid fauna from this region suffers from similar problems to many amphipod groups recorded in the Southern Hemisphere. These problems primarily have arisen from Northern Hemisphere researchers (during the years 1760–1920), examining the fauna, and after seeing similarities to known, familiar fauna, assume they are the same organism, creating a concept of ‘cosmopolitan’ species. The fauna is rarely examined in detail as it is abundant, diverse and not considered commercially important. Therefore, the assumed ‘cosmopolitan’ species names are used regularly and repeatedly in ecological and other studies, forming assumptions regarding distributions and influence. This situation is compounded by the introduction of invasive species and the need to assess potential related impacts. Therefore, to resolve some of these issues, this study uses an integrative (using both morphological and molecular methods where possible) approach to review the known species of the family Caprellidae from New Zealand waters and describes six new species: Caprella perplexa sp. nov., Caprella sarahae sp. nov., Caprella serenae sp. nov., Caprellina judyae sp. nov., Caprellina plumea sp. nov., Noculacia anima sp. nov. and one resurrected species, Caprella novaezealandiae to the fauna. A dichotomous key to the New Zealand caprellid fauna is provided, and molecular and morphological analysis and biogeographic comments on the origins of the fauna are also provided. This paper specifically examines the complex of caprellid species from Aotearoa New Zealand and almost doubles the described fauna from 8 species to 15 species.